Teams, Systeme, Implementation etc.: Eine integrierte Diskussion der organisationstheoretisch inspirierten aktuellen Reformen des Mathematikunterrichts und ihrer Traditionen (mathematica didactica, 2007)
Current attempts to reform of mathematics education are based on scientific concepts from the theory of organisations. Since concepts are always bound to the fields in which they have been developed, this is a problematic issue. The perspectives on humans and their development might differ considerably between economic and educational theory. This paper reports on the conflicts and consequences that might emerge from conceiving educational reform mainly an organisational matter.